Prevalence of Insomnia and Sleep Habits during the First and Second Wave of COVID-19 in Belgium. Issue 1 (21st February 2023) - Roland, Aurore; Colomb, Clara; Noël, Stéphane; Putilov, Arcady; Oginska, Halszka; Delwiche, Bérénice; Benkirane, Oumaima; Windal, Maxime; Vanlaer, Nathalie; Briganti, Giovanni; Carrasquer-Ferrer, Judith; Riahi, Behrouz; et al.
Belgium has one of the highest numbers of COVID-19 cases per 1 million inhabitants. The pandemic has led to significant societal changes with repercussions on sleep and on mental health. We aimed to investigate the effect of the first and the second wave of COVID-19 on the sleep of the Belgian populationWe launched two online questionnaires, one during the first lockdown (7240 respondents) and one during the second (3240 respondents), to test differences in self-reported clinical insomnia (as measured by the Insomnia Severity Index) and sleep habits during the two lockdowns in comparison with the pre-COVID period. The number of persons with clinical insomnia rose during the first lockdown (19.22%) and further during the second (28.91%) in comparison with pre-lockdown (7.04–7.66%). Bed and rise times were delayed and there was an increased time in bed and sleep onset latency. There was further a decrease in total sleep time and in sleep efficiency during both confinements. The prevalence of clinical insomnia quadrupled during the second wave in comparison with the pre-lockdown situation. Sleep habits were most altered in the younger population, indicating a greater risk for this group to develop a sleep-wake rhythm disorder.